1999
DOI: 10.1091/mbc.10.6.1891
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Activated Integrin Lymphocyte Function-associated Antigen 1 with Ligand Intercellular Adhesion Molecule 1 Induces Activation and Redistribution of Focal Adhesion Kinase and Proline-rich Tyrosine Kinase 2 in T Lymphocytes

Abstract: Integrin receptors play a central role in the biology of lymphocytes, mediating crucial functional aspects of these cells, including adhesion, activation, polarization, migration, and signaling. Here we report that induction of activation of the ␤2-integrin lymphocyte function-associated antigen 1 (LFA-1) in T lymphocytes with divalent cations, phorbol esters, or stimulatory antibodies is followed by a dramatic polarization, resulting in a characteristic elongated morphology of the cells and the arrest of migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
70
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 76 publications
9
70
0
Order By: Relevance
“…6). Rap1 and VAV-1 have also been implicated in outside-in signaling (24,46). Cytoskeleton protein talin binds LFA-1 and controls LFA-1 activation (47), and our preliminary data also showed that M12 reduced the association of LFA-1-talin in resting states.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…6). Rap1 and VAV-1 have also been implicated in outside-in signaling (24,46). Cytoskeleton protein talin binds LFA-1 and controls LFA-1 activation (47), and our preliminary data also showed that M12 reduced the association of LFA-1-talin in resting states.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to mediating ICAM-1 adhesion, it can generate outside-in signals that costimulate T cells (25,41,42). The nature of the outside-in pathway has been unclear, but may involve PYK-2 (proline-rich tyrosine kinase 2) and FAK (24,25). ADAP and its binding to SLP-76 can regulate TcR mediated inside-out signaling for integrin activation (9,10,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results raise the possibility that LFA-1 may transduce specific costimulatory signals that can impact both on T cell activation and differentiation. Cross-linking of LFA-1 has been shown to activate phospholipase C (27)(28)(29), PI3K and JNK (30), Pyk2 (31), DNAM (CD226) (32), cytohesion and ERK (33,34), and JAB1 (34,35). But whether these signals are induced during T cell Ag recognition in the context of APC and how these signals might be integrated with TCR-derived signaling are not yet clear.…”
mentioning
confidence: 99%